Intersectional Program Evaluation: Considering Race, Class, Sex, and Language in Gifted Program Effectiveness - Tristta M. Kuykendall (MDPI AG, 2023)
Gifted education is an effective intervention for high-ability students who need more academic challenges. However, the relationship between program effectiveness and demographic categories has been scantly evaluated. Research focused on the effectiveness of gifted education infrequently considers the intersections of ability, race, sex, socioeconomic status, and language. To fill this gap, I used an ex post facto quasi-experimental design to conduct a cross-sectional evaluation of gifted service models at the intersections of cultural identity groups in Ohio. Findings underscore the relationship between the type of gifted service model and achievement on standardized math test scores varying across demographic groups.